Kearifan Lokal Masyarakat Towani Tolotang di Kabupaten Sidenren Rappang - Muh Rusli (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2012)
The aspects of local wisdom of Towani Tolotang society can be classified by three aspects, but it could be manifested in concept â€œPerrinyamengâ€. Relation to the God, it includes the value of loyalty to Dewata Seuwae and respect to Waâ€™ as the leader at once. Relation to humanity includes the value of togetherness, peace, social sensitivity, justice and others. Where as, the value of relation to nature is saving nature for human intention. The three given relations of local wisdom implicate greater for lives of Towani Tolotang society, although not all of them is able to apply that value. Studying from local wisdom of Towani Tolotang society, found alternative ideas for conflict solution in Indonesia, â€œPerrinyamengâ€ to be meant is the will for serious working, highly respected to the human beings, and widely social sensitivity for humanâ€™s destiny. This given concept has relevance if it is integrated with values of Islam. â€œPerrinyamengâ€ is one of the most idealistic concepts to be applicable in handling Indonesia conflicts.